Fat to fit – an Asian obesity management program and the Malaysian case study - Salle, D.D.A.; Bong, Y.B.; Mohamed, A.M.; Shariff, A.A.; Merican, A.F. (2015)
Fat to Fit was a 3-month weight loss program initiated for an Asian obesity management program. The aim of this study is to investigate the effect of physical activity and changes of body size and body composition. A total of 28 subjects ranging from 20-50 years old completed the 3-month program, which required them to follow a structured exercise thrice per week. Subjects were screened and selected through interviews. Anthropometric measurements for body weight, size [height, body dimension circumferences, body mass index (BMI), body composition (fat mass and lean mass)] and skin fold thickness were obtained using conventional method. Body composition was evaluated via Omron HBF 514C body composition monitor and scale. A guided 3-months physical exercise was used as the intervention. Pre- and post- test analysis was computed through paired t-test using IBM SPSS Statistics 22. Changes in body size were examined and the descriptive statistics were reported. Following the intervention, body mass and body composition was significantly lower than the baseline values. This study will be used as a national community intervention programme to combat obesity in Malaysia. This research will contribute to new information on obesity management in Asia Pacific region, which is rather limited at this moment.